x^4-7x^2+12
=x^4-4x^2-3x^2+12
=x^2(x^2-4)-3(x^2-4)
=(x^2-4)(x^2-3)
=(x+2)(x-2)(x^2-3)=0
x=-2, x=2, x= -sqrt3, x=sqrt3
2007-02-14 17:20:34
·
answer #1
·
answered by nazia f 4
·
0⤊
0⤋
x^4 - 7x^2 + 12 = 0
This is actually a quadratic in disguise; all you have to do is split up x^4 into x^2 and x^2. We're going to have this form:
(x^2 + ?)(x^2 + ?) = 0
Treating this like a quadratic, we know that -4 and -3 multiply to make +12, and add to make -7. So we have
(x^2 - 4)(x^2 - 3) = 0
Solving these individually, we get
x^2 - 4 = 0
x^2 - 3 = 0
(x - 2)(x + 2) = 0
x^2 - 3 = 0
x = {-2, 2}
x = {-sqrt(3),sqrt(3)}
So our four solutions are
x = {-2, 2, -sqrt(3), sqrt(3)}
2007-02-14 16:37:18
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
x^4-7x^2+12=0
(x^2-3)(x^2-4)=0
(x^2-3)(x+2)(x-2)=0
2007-02-14 18:01:23
·
answer #3
·
answered by Helper X 2
·
0⤊
0⤋
take x^2 as (A)and then substitute the equation which now becomes
A^2-7A+12=0
NOW SOLVE IT LIKE A QUADRATIC EQUATION.
2007-02-14 16:37:05
·
answer #4
·
answered by boss_00007 2
·
0⤊
0⤋
the easiest is to just plot it in a graphing calculator and find out where it intersects the x axis.
2007-02-14 16:35:01
·
answer #5
·
answered by stitchfan85 6
·
0⤊
1⤋